Self‐Lubricative Organic–Inorganic Hybrid Coating with Anti‐Icing and Anti‐Waxing Performances by Grafting Liquid‐Like Polydimethylsiloxane. Issue 18 (23rd May 2022) - Hao, Xiaoqing; Sun, Zhengrong; Wu, Shuwang; Wang, Ta‐Wei; Liu, Yubo; Wu, Yang; He, Ximin; Liu, Qinze; Zhou, Feng
Abstract: Polydimethylsiloxane (PDMS) is one of the most popular materials to protect infrastructures from the complicated environment due to its chemical stability, nontoxicity, low cost, high durability, and chain flexibility. Herein, a series of organic–inorganic hybrid coatings are prepared by simply grafting loop‐like PDMS on a solid surface. Owning to the low surface energy and high mobility of PDMS chains, the special characteristics, including liquid repellency, anti‐fouling, self‐lubrication, anti‐ and delay‐ice, anti‐paraffin, etc., are presented. To confirm the liquid‐like slippery nature of PDMS surface, the controlled de‐icing and de‐waxing tests on rigid chain surfaces are conducted. The liquid‐like nature of PDMS allows ice or paraffin to have a low adhesion in a slip state, but a fractured state on alkylated and perfluorinated surface with a high adhesion strength. In addition, the flexible PDMS chains grafted on the inorganic silica layer by stable covalent bond endow the surface with excellent durability, including maintaining low ice adhesion during 50 icing‐deicing cycles, resistance to UV irradiation, washing or soaking in organic solvent, etc. This work provides a simple approach for constructing self‐lubricative low surface energy coating to realize de‐ice and de‐wax easily, which may have a broad prospect of application in equipment protection. Abstract : A series of organic–inorganic hybrid coatings are prepared by simply grafting loop‐like polydimethylsiloxane (PDMS) on silica sol interlayer. The low surface energy and high mobility of PDMS chains allow ice or paraffin block to slip with low adhesion. But a fracture state of ice or paraffin block with high adhesion strength is displayed on the rigid alkylated and perfluorinated surface.